Carbonation treatment of gasification fly ash from municipal solid waste using sodium carbonate and sodium bicarbonate solutions - Qin, Junde (2022)
In recent years, slagging-gasification technology has received increasing attention in treating municipal solid waste (MSW). Compared with conventional incineration, the higher temperature in the slagging-gasification process optimizes its residue composition, and gasification fly ash (GFA) is the only unreused solid residue. Although GFA is a potential civil engineering material, its high content of heavy metals, chlorides, and sulfates hinders its practical use. Moreover, although carbonation has proven to immobilize heavy metals in incineration fly ash, the conventional gas carbonation method cannot remove chlorides and sulfates. In this study, sodium bicarbonate (NaHCO3) treatment was studied to treat GFA for the first time, and sodium carbonate (Na2CO3) was used for comparison. Different concentrations of NaHCO3 and Na2CO3 solutions were used to treat the GFA, and comprehensive tests were conducted on the treated samples. The results indicated that NaHCO3 treatment was effective in immobilizing Pb, Zn, Cu, and Ni in GFA, while Na2CO3 treatment could not effectively immobilize Pb and Zn. Both NaHCO3 and Na2CO3 promoted the removal of chlorides and sulfates in GFA. The wastewater from the NaHCO3 treatment contained fewer heavy metals compared with those from water washing or Na2CO3 treatment, benefitting its treatment or reuse.